The subjectively perceived injectability as an early indicator for adverse events?. (6th February 2022) - Alfertshofer, Michael G.; Sattler, Gerhard; Frank, Konstantin; Melnikov, Dimitry V.; Freytag, Lysander; Mercado‐Perez, Arnaldo; Hargiss, John B.; Dumbrava, Mihai; Cotofana, Sebastian
Abstract: Background: With an increasing demand of aesthetic soft‐tissue filler treatments, the occurrence of adverse events rises likewise. An optimized injection algorithm adapted to product characteristics (eg, rheology) of the soft‐tissue filler is crucial in order to ensure satisfying clinical outcomes and high patient safety. Objective: To identify a subjective feedback mechanism for the avoidance of adverse events after soft‐tissue filler injection procedures. Methods: A retrospective data analysis of n = 387 aesthetic treatments performed on n = 291 patients (4 males, 287 females) with different soft‐tissue fillers with regard to loss of volume (filling effect), injected layer, injectability ("ease of injection"), injected volume, and injection technique was conducted. Results: The subjectively perceived injectability during the injection process was statistically significantly related to G‐Prime value with rs = 0.101 with p = 0.048, indicating an increased difficulty while injecting products with higher G‐Prime. The occurrence of adverse events was also statistically significantly related to the injectability: injections with increased subjectively perceived difficulty showed increasing odds of developing adverse events by OR 0.157 with p = 0.002. Conclusion: Injections that were subjectively more difficult to perform are more likely to develop adverse events. Respecting the layered arrangement of the face, the recommended and approved depth and facial region for each specific treatment enable practitioners to achieve satisfying outcomes while keeping the rate of adverse events low.